2020
DOI: 10.3390/ani10040742
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Properties of Campylobacter Spp. Originating from Domestic Geese in Poland

Abstract: A total of 240 samples were evaluated for the presence of Campylobacter spp. Campylobacter was found in 83.3% of the cecum contents samples and 52.5% of the neck skin samples from carcasses. The prevailing species was C. jejuni, accounting for 87.7% of all Campylobacter isolates, and the remaining 12.3% of isolates were C. coli. All Campylobacter isolates, independent of the sample origin and species, were positive for 6 out of 15 tested genes (flaA, flhA, cadF, racR, ciaB, and cdtA genes). The prevalence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
3
14
0
1
Order By: Relevance
“…In the present study, we revealed high resistance rates to ciprofloxacin (60% in C. jejuni vs. 86.7% in C. coli ) and nalidixic acid (87.9% in C. jejuni vs. 80% in C. coli ). Such results are consistent with reports from Algeria, Poland, and Belgium [ 28 , 29 , 30 ]. Quinolone-resistance has been linked with the presence of two different mechanisms, namely the presence of the cmeABC operon and point mutations in the quinolone-resistance determining region (QRDR) of the DNA gyrase A ( gyrA ) gene.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we revealed high resistance rates to ciprofloxacin (60% in C. jejuni vs. 86.7% in C. coli ) and nalidixic acid (87.9% in C. jejuni vs. 80% in C. coli ). Such results are consistent with reports from Algeria, Poland, and Belgium [ 28 , 29 , 30 ]. Quinolone-resistance has been linked with the presence of two different mechanisms, namely the presence of the cmeABC operon and point mutations in the quinolone-resistance determining region (QRDR) of the DNA gyrase A ( gyrA ) gene.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rates of wlaN and cgtB genes were noted at similar levels in previous studies. These genes were detected in 11.3% of wildlife waterfowl isolates in South Korea [37], in 25% of human isolates in Japan [53], in 17.5% of geese carcasses in Poland [54], in 6.7% of human isolates in Argentina [55], and up to 21.9% of livestock animals in Spain [56].…”
Section: Discussionmentioning
confidence: 99%
“…The wlaN gene (prevalence of 13.9%) is responsible for the metabolism of specific lipooligosaccharides (LOS) connected with disease sequelae such as Guillain-Barre syndrome (38,39). Concerning the genes connected with adherence and colonization (40) the study results confirmed 44.4% prevalence of the dnaJ gene and lower prevalence of the racR gene (27.8%). The virB11 gene, which is responsible for the expression of invasion (41), was not detected in the C. jejuni isolates.…”
Section: Discussionmentioning
confidence: 54%